Respuesta :

The chain rule states that

[tex]\dfrac{\mathrm dw}{\mathrm dt}=\dfrac{\partial w}{\partial x}\dfrac{\mathrm dx}{\mathrm dt}+\dfrac{\partial w}{\partial y}\dfrac{\mathrm dy}{\mathrm dt}+\dfrac{\partial w}{\partial z}\dfrac{\mathrm dz}{\mathrm dt}[/tex]

Since [tex]\ln(x^2+y^2+z^2)^{1/2}=\dfrac12\ln(x^2+y^2+z^2)[/tex], you have

[tex]\dfrac{\partial w}{\partial x}=\dfrac x{x^2+y^2+z^2}[/tex]
[tex]\dfrac{\partial w}{\partial x}=\dfrac y{x^2+y^2+z^2}[/tex]
[tex]\dfrac{\partial w}{\partial z}=\dfrac z{x^2+y^2+z^2}[/tex]

and

[tex]\dfrac{\mathrm dx}{\mathrm dt}=\cos t[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dt}=-\sin t[/tex]
[tex]\dfrac{\mathrm dz}{\mathrm dt}=\sec^2t[/tex]

Also, since [tex]x^2+y^2+z^2=\sin^2t+\cos^2t+\tan^2t=1+\tan^2t=\sec^2t[/tex], the derivative is

[tex]\dfrac{\mathrm dw}{\mathrm dt}=\dfrac{\sin t\cos t}{\sec^2t}-\dfrac{\sin t\cos t}{\sec^2t}+\dfrac{\tan t\sec^2t}{\sec^2t}[/tex]
[tex]\dfrac{\mathrm dw}{\mathrm dt}=\tan t[/tex]